Symptom-related patient-provider communication among women with breast cancer receiving chemotherapy. (December 2021) - Whisenant, Meagan S.; Coombs, Lorinda A.; Wilson, Christina; Mooney, Kathi
Abstract: Purpose: The purpose of this study was to determine the extent to which women being treated for breast cancer discussed their symptoms during the week prior to a clinic visit. Method: Women reported the severity of 11 symptoms (0–10 scale) daily using an automated patient-reported outcomes system. Clinic visits were audio recorded, and symptom discussions were coded. Moderate to severe symptoms reported in the week prior to the visit were compared to the symptoms discussed at the visit. Results: Twenty-six clinic visits of 10 women (mean age, 51.6 years; half had advanced disease) were recorded. In the week prior to their visits, participants provided 183 reports of moderate to severe symptoms. Reported symptoms were discussed at 49.5% of visits, with 36% of discussions initiated by patients. These discussions were more likely to include assessment and normalizing and were less focused on intensifying symptom management. Symptom discussions were more likely with younger women and the time spent discussing symptoms decreased over subsequent visits for all women. Conclusions: Women who are symptomatic during treatment are not systematically queried about their symptoms, nor are women effectively reporting their symptoms. Attention should be directed at eliciting symptoms from older women; symptoms should be discussed throughout the duration of chemotherapy. Highlights: Women receiving breast cancer treatment are not systematically queried about nor do they effectively report their symptoms. Clinicians should not assume patients are not experiencing symptoms if they are not mentioned spontaneously at visits. Because they may be less likely to discuss symptoms, attention should be given to eliciting symptoms from older women.